ChemInform Abstract: Physical Properties of the Ternary Borides Ni21Zn2B20 and Ni3ZnB2. Issue 10 (7th March 2013) - Malik, Z.; Grytsiv, A.; Michor, H.; Rogl, G.; Puchegger, S.; Mueller, H.; Kriegisch, M.; Bauer, E.; Eisenmenger‐Sittner, C.; Rogl, P.
Abstract Mechanical, electrical, and magnetic properties of the title compounds are determined by XRD, resonant ultrasonic spectroscopy, Vickers hardness, specific heat, electrical resistivity, specific heat, and magnetic measurements.